Assessment of IBM-FRS total score and specific functional domains in a large cohort of inclusion body myositis patients - Vicino, Alex; Lauletta, Antonio; Bonanno, Silvia; Barbaccia, Adele; Valentino, Maria Lucia; Risi, Barbara; Torchia, Eleonora; Cheli, Marta; Tonin, Paola; Urbano, Guido; Saccani, Elena; Faedo, Elena; et al. (Journal of neurology, 2025)
Inclusion body myositis (IBM) is an acquired myopathy of older adults, associated with progressive weakness and functional limitations. The inclusion body myositis functional rating score (IBM-FRS) is a reliable tool for the assessment of disease severity, but poor data are available on its correlation with clinical features. In this cross-sectional, retrospective multicenter study, we analyzed IBM-FRS total score (TS) and its items in a cohort of 147 IBM patients, considering 4 functional domains (FD) (dysphagia, upper limb function, daily living and independence, lower limb function). We analyzed TS and FD values’ correlations with demographic and clinical variables (onset, loss of walking ability, non-invasive ventilation, percutaneous gastrostomy—PEG) as well as between each FD and the remaining TS. Lower, hence worse, scores in the dysphagia domain (FD1) correlated with female gender ( p < 0.01), dysphagia as presenting symptom ( p < 0.01), and PEG use ( p < 0.0001), but interestingly without correlation with time variables IBM-FRS total score or other domains. This may define a distinct phenotype with different onset and outcome. Worse scores in the upper and lower limb and daily living domains (FD2–FD4) were strongly associated with loss of ambulation, higher age at baseline, and longer disease duration ( p < 0.001). We identified a cutoff value of 28/40, allowing to differentiate patients with less disease burden, potentially able to show better response in future clinical trials. Our study enriches the literature by correlating IBM-FRS total scores and its items with patient characteristics, offering important implications for clinical management, subgroup analysis, and future trials design.